Impact of the Value of Intangible Assets on the Capitalization of Food Retailers for their sustainable Growth - O. V. Loseva (Финансы: теория и практика, 2021)
The objective of the research in the article is the food retail companies that occupy leading positions in the Russian and foreign markets. The subject of the study is financial and economic relations in the field of the use of intangible assets (IA) as a significant factor in increasing the capitalization of food retailers and their sustainable development. The relevance of the problem is due, on the one hand, to the significant contribution of trade to the country’s GDP, on the other hand, to the need to find new drivers for the sustainable development of food retailers in the context of overcoming the negative consequences of the pandemic and the digital economy. The purpose of the study is to assess the impact of the value of intangible assets on the capitalization of food retailers. The authors applied the methods of comparative analysis, calculation of financial and economic indicators, correlation, and regression analysis of statistical data processing. The authors used Student’s t-test and Fisher’s f-test to confirm the quality of the constructed model. The study shows that Russian food retailers, as compared to foreign ones, occupy a smaller market share in the domestic economy and have a smaller share of intangible assets in the non-current assets of companies (except for X5 Retail Group). On the Russian food market, a trend has been revealed towards an increase in the production of goods under private labels and a decrease in the presence of foreign retailers, as well as an increase in the share of online trading that requires the use of intellectual property, including digital intangible assets, and leads to an increase in cash flows. Based on multivariate correlation analysis, it was found that the capitalization of trading companies in the food sector is most affected by the value of intangible assets and return on them. The constructed model of linear two-factor regression allows the authors to conclude that with an increase in the value of intangible assets by 1%, the market capitalization of a company increases by 10% with a constant return on assets. The article provides recommendations for Russian food retailers on the formation and use of a portfolio of intangible assets for value-based business management, which will contribute to their sustainable development.